Maternal obesity is not associated with placental lipid accumulation in women with high omega-3 fatty acid levels. (September 2018) - Alvarado, Fernanda L.; Calabuig-Navarro, Virtu; Haghiac, Maricela; Puchowicz, Michelle; Tsai, Pai-Jong S.; O'Tierney-Ginn, Perrie
Abstract: Introduction: Placentas of obese women have higher lipid content compared to lean women. We have previously shown that supplementation of overweight and obese women with omega-3 fatty acids decreases placental esterification pathways and total lipid content in a mid-western population (Ohio). We hypothesized that placental lipid accumulation and inflammation would be similar between lean and obese women living in a region of high omega-3 intake, such as Hawaii. Methods: Fifty-five healthy, normal glucose tolerant women from Honolulu Hawaii, dichotomized based on pre-pregnancy BMI into lean (BMI <25 kg/m 2, n = 29) and obese (BMI >30 kg/m 2, n = 26), were recruited at scheduled term cesarean delivery. Maternal plasma DHA levels were analyzed by mass spectrometry. Expression of key genes involved in fatty acid oxidation and esterification were measured in placental tissue using qPCR. Total lipids were extracted from placental tissue via the Folch method. TNF-α concentration was measured by enzyme-linked immunosorbent assay in placental lysates. Results: DHA levels were higher in lean women compared to obese women (P = 0.02). However, DHA levels in obese women in Hawaii were eight times higher compared to obese Ohioan women (P=<0.0001). Placental lipid content and expression of key genes involved in fatty acid oxidation and esterification were similar (P > 0.05) between lean and obese women in Hawaii. Furthermore, TNF-α placental lysates were not different between lean and obese women. Conclusions: Though obese women in Hawaii have lower DHA levels compared to their lean counterparts, these levels remain over eight times as high as obese Ohioan women. These relatively high plasma omega-3 levels in obese women in Hawaii may suppress placental lipid esterification/storage and inflammation to the same levels of lean women, as seen previously in vitro . Highlights: In Hawaii, maternal obesity is not associated with higher placental lipid accumulation. Placental TNF-α concentration is similar between obese and lean women in Hawaii. Pregnant women in Hawaii have 8-fold higher plasma DHA levels than women in midwest. Placental TNF-α is lower in obese women in Hawaii than in obese Midwestern women.